Pemberian Syarat Reflektif Kecepatan Fluida di Batas Anomali Kedalaman dalam Simulasi Persamaan Air Dangkal - Nugroho Adi Pramono (Universitas Negeri Malang, 2016)
The simulation of shallow water equation with straight configuration reflective depth anomaly has been performed. This program simulated wave absorber in the beach in order to prevent furthur abrasion of by sea. This program using modified Navier-Stokes equation and running on Matlab program. The result show that depth-anomaly reduced the amount on wave amplitudo by significant value.DOI: http://dx.doi.org/10.17977/um024v1i12016p007